Development of integrated systematic approach conceptual design and TRIZ using safety principles in embodiment design for complex products - Kamarudin, Khairul Manami (2017)
There are many conceptual design methods available for the engineering design world. Of all the methods, two significant methods are chosen to be integrated for the effective conceptual design process. These are the Systematic Approach (SA) and the Theory of Inventive Problem Solving (TRIZ). SA consists of the Systematic Approach Conceptual Design (SACD) and Systematic Approach Embodiment Design (SAED), which were established by Pahl and Beitz, and widely used in industry and by academics. In addition, TRIZ is actively practiced in companies that wish to innovate creative and inventive designs. Although both methods have contrasting features there are some similarities that enable them to be united and harmonized. Many scholars have attempted to develop a new methodology by combining SA and TRIZ but none have integrated the safety principles of SAED with the inventive principles of TRIZ. In designing complex artefacts, constraints and safety are the main issues in the design change process. Implementing safety at a later stage might compromise the concept ideas and end up being a conventional and common concept design. This study developed a conceptual design method, TRIZ-SA, with a specialized safety approach combining the Function Constraint Model (FCM) and the Safety Principle Guide (SPG) as the method’s tools. The method aims to encourage the intervention of safety in the conceptual design process to stimulate ideas for solutions that are efficient in safety and creativity. The development of TRIZ-SA is through qualitative content analysis of the work of many scholars and patents. The pairwise comparative analysis is also conducted in the development of the 8-Step. The validation of the combined method for the safety approach is done through a conceptual design case study on the geometric and shape design of an aircraft’s Main Landing Gear (MLG). The combination of SA and TRIZ resulted in an easier solution finding process for an artefact that requires high concern in terms of safety, thereby opening up a new perspective in the designing concept of a complex artefact and shaping the design path towards a safe and creative concept design. The implications of this study will help designers optimize and develop a safe and inventive concept design in an effective and creative way.